A network meta-analysis on the comparative effect of nutraceuticals on lipid profile in adults. (September 2022) - Osadnik, Tadeusz; Goławski, Marcin; Lewandowski, Piotr; Morze, Jakub; Osadnik, Kamila; Pawlas, Natalia; Lejawa, Mateusz; Jakubiak, Grzegorz K.; Mazur, Agnieszka; Schwingschackl, Lucas; Gąsior, Mariusz; Banach, Maciej
Abstract: It is estimated that 2.6 million deaths worldwide can be attributed to hypercholesterolemia. The main reason for non-adherence to statin therapy are the statin-associated muscle symptoms (including nocebo/drucebo effect). In this case, apart from ezetimibe, nutraceuticals are prescribed. We aimed to assess the comparative efficacy of different nutraceuticals in terms of lowering low density lipoprotein cholesterol (LDL-C) and improving lipid profile. Electronic and hand searches were performed until February 2021. The inclusion criteria were the following: (1) randomized trial with any of the reportedly LDL-C lowering nutraceutical: artichoke, berberine, bergamot, garlic, green tea extract, plant sterols/stanols, policosanols, red yeast rice (RYR), silymarin or spirulina. (2) outcome either LDL-C (primary outcome), total cholesterol (TC), high density lipoprotein cholesterol (HDL-C) or serum triglycerides (TG). Random effects network meta-analysis (NMA) was performed to rank the effect of each intervention using frequentist approach. Finally, a total of 131 trials enrolling 13, 062 participants were included. All analysed nutraceuticals except for policosanols were more effective in lowering LDL-C (−1.21 [−46.8 mg/dL] to −0.17 [−6.6 mg/dL] mmol/l reduction) and TC (−1.75 [−67.7 mg/dL] to −0.18 [7 mg/dL] mmol/l reduction) than placebo/no intervention. The most effective approaches in terms of LDL-C- and TC-lowering were bergamot and RYR (−1.21 [−46.8 mg/dl] and −0.94 [−36.4 mg/dl] mmol/l) reduction respectively. In conclusion, bergamot and RYR appear to be the most effective nutraceuticals in terms of LDL-C and TC reduction. Evidence for bergamot effect was based on relatively small study group and may require further investigations. Policosanols have no effect on the lipid profile. Graphical Abstract: ga1